Student Academic Procrastination That Boils Down to Gadget Addiction: Post-Pandemic Challenges to Solve - Wahyuni, Sri; Hura, Rosnila; Simanjuntak, Herbin; Zendrato, Muliani; Purba, Vernando; Sitepu, Meri KD (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2022)
The prolonged pandemic conditions experienced by the world forced changes in various aspects of life and unwittingly formed a new "culture" in the world of education that tended to lead to academic procrastination. This study aims to examine the continued impact of procrastination that affects gadget addicts. This study used a quantitative approach with Christian religious high school students acting as research respondents. Data was obtained using random sampling techniques with a total sample of 100 people. Students who were respondents were active students in lectures and at the same time active in using gadgets. The research instrument used is in the form of a questionnaire with a focus on academic procrastination and the potential of gadget addicts. The results of research in the field show that the influence of academic procrastination on gadget addicts is 51.6%.